2021
DOI: 10.1080/1068316x.2021.1972108
|View full text |Cite
|
Sign up to set email alerts
|

Racial fairness in violence risk instruments: a review of the literature

Abstract: Violence risk instruments are used in numerous countries to estimate an individual's likelihood of reoffending. The racial fairness of violence risk instruments has received increasing attention due to ostensible differences among Anglo populations and racial minorities (e.g., African Americans and Indigenous populations). Fairness, which has numerous definitions (sensitivity fairness, error rate balance, calibration, predictive parity, statistical parity), can affect a risk instrument's utility in varying way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…There have been attempts to reconcile and summarize varying definitions of test bias or racial/ethnic fairness, both specific to risk assessment (e.g., Ashford et al, 2022) and more broadly (Warne et al, 2014). Given that mean group differences in scores (also referred to as statistical parity ) are more a reflection of systemic inequality rather than test bias (Warne et al, 2014) and that risk scales are fundamentally intended to predict recidivism, what is of primary importance for evaluating cross-cultural validity is examining differential predictive accuracy of the scale (and ideally the individual items as well).…”
Section: Importance Of Examining Predictive Accuracy Of Risk Scales A...mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been attempts to reconcile and summarize varying definitions of test bias or racial/ethnic fairness, both specific to risk assessment (e.g., Ashford et al, 2022) and more broadly (Warne et al, 2014). Given that mean group differences in scores (also referred to as statistical parity ) are more a reflection of systemic inequality rather than test bias (Warne et al, 2014) and that risk scales are fundamentally intended to predict recidivism, what is of primary importance for evaluating cross-cultural validity is examining differential predictive accuracy of the scale (and ideally the individual items as well).…”
Section: Importance Of Examining Predictive Accuracy Of Risk Scales A...mentioning
confidence: 99%
“…Given that mean group differences in scores (also referred to as statistical parity ) are more a reflection of systemic inequality rather than test bias (Warne et al, 2014) and that risk scales are fundamentally intended to predict recidivism, what is of primary importance for evaluating cross-cultural validity is examining differential predictive accuracy of the scale (and ideally the individual items as well). Differential predictive accuracy can be defined and assessed in numerous ways (e.g., Ashford et al, 2022), but we follow the primary analyses of discrimination and calibration recommended by Hanson (2022) and Helmus and Babchishin (2017).…”
Section: Importance Of Examining Predictive Accuracy Of Risk Scales A...mentioning
confidence: 99%
“…Both jurors and evaluators would also have opportunities to clearly view the examinee, making physical attributes and mannerisms more salient. Research that more closely resembles the assessment and/or trial process is needed, especially considering research suggesting individuals of color may be found to be at higher risk because of their race (Ashford et al., 2022; Harcourt, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Barnes et al., 2016 ; Chenane et al., 2015 ; Gutierrez et al., 2013 ; Lowder et al., 2019 ; Meyers & Schmidt, 2008 ; Olver et al., 2014 ; Onifade et al., 2009 ), several studies suggest that this prediction is marginally less accurate (Shepherd, Adams, et al., 2014 ; Shepherd, Luebbers, Ferguson, et al., 2014 ; Wilson & Gutierrez, 2014 ; Wormith et al., 2012 ). Furthermore, studies have found that BIPOC offenders are misclassified more regularly than White offenders on actuarial instruments (Ashford et al., 2021 ; Campbell et al., 2018 ; Fass et al., 2008 ; Whiteacre, 2006 ; Wilson & Gutierrez, 2014 ).…”
Section: Risk Assessment and Culturementioning
confidence: 99%